Analysis Of Fishing Frequency, Fishing Gear Capacity, And Seafish Prices As Determinants Of Income For Fishers At The Pasar Bawah Manna Fishing Port In South Bengkulu - Wino Afrianto; Herri Fariadi; Rika Dwi Yulihartika (Jurnal Multidisiplin, 2026)
Fish Auctions (TPI) play a key role in fisheries activities and serve as a critical factor in driving and improving fishermen’s livelihoods and well-being. This study aims to analyze the income levels of capture fishermen and to examine the determinants of fishing frequency, fishing gear capacity, and marine fish prices on the income of capture fishermen at the Pasar Bawah Manna Fish Auction in South Bengkulu Regency. The research method employed was a quantitative approach using descriptive analysis and multiple linear regression analysis. The results of this study indicate an average catch of 336 kg per fisherman per month and income of Rp.5,717,489 per fisherman per month. The fishing frequency variable (X1) had a calculated t-value of 3.049 with a p-value of 0.003; the fishing gear capacity variable (X2) had a calculated t-value of 2.284 with a p-value of 0.025; and the marine fish price variable (X3) had a calculated t-value of 2.393 with a p-value of 0.019. The t-table value of 1.666 at a significance level of 0.05 indicates that the calculated t-values for the fishing frequency, fishing gear capacity, and sea fish price variables are greater than the t-table value; therefore, all variables influence the income of capture fishermen.